Who benefits? Heterogeneous effects of international student mobility on occupational attainment - Stine Waibel; Heiko Rüger; Andreas Ette (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2020)
It is well documented that students with favourable socio-economic and educational characteristics more often take advantage of international mobility opportunities. We explore whether the effect of ISM on professional success depends on selection into ISM (educational achievements, family background, etc.). Analyses are based on data from the German National Educational Panel Study (NEPS), which is a representative sample of the population living in Germany born between 1944 and 1986. Respondents who spent at least one month abroad during a higher education spell are considered internationally mobile. We use propensity score matching and stepwise stratification methods to analyse the potential heterogeneity of treatment effects. We find that higher education graduates with low propensity to be internationally mobile realize substantially greater occupational status benefits than graduates with higher propensity. This may work against social inequality in times of mass higher education.
Keywords: 650; Study abroad; student mobility; occupational success; effect heterogeneity; social selectivity; propensity score matching; Familienunternehmen; Unternehmensnachfolge; Simulation; Führungskräfte; Qualifikation; Befragung; Personalberatung; Deutschland